Wavelet packet transform for detection of single events in acoustic emission signals. (December 2015) - Bianchi, Davide; Mayrhofer, Erwin; Gröschl, Martin; Betz, Gerhard; Vernes, András
Abstract: Acoustic emission signals in tribology can be used for monitoring the state of bodies in contact and relative motion. The recorded signal includes information which can be associated with different events, such as the formation and propagation of cracks, appearance of scratches and so on. One of the major challenges in analyzing these acoustic emission signals is to identify parts of the signal which belong to such an event and discern it from noise. In this contribution, a wavelet packet decomposition within the framework of multiresolution analysis theory is considered to analyze acoustic emission signals to investigate the failure of tribological systems. By applying the wavelet packet transform a method for the extraction of single events in rail contact fatigue test is proposed. The extraction of such events at several stages of the test permits a classification and the analysis of the evolution of cracks in the rail. Abstract : Highlights: Use of the wavelet packets for fltering noisy acoustic emission signal. Use of time/frequency analysis for identifying single acoustic emission events. Analysis of the time evolution of rail contact fatigue test. Correlation between event density and visual crack distance on rail.